Removal of Pb(II) from Aqueous Solutions with Manganese Oxide-Modified Diatomite - Huynh Thanh Danh; Nguyen Thi Truc Ly; Vanthan Nguyen; Dinh Quang Khieu; Pham Dinh Du (Adsorption Science & Technology)
In the present work, natural diatomite modified with manganese oxide (MnO2) was prepared via direct redox reaction with KMnO4 and HCl. The product was characterized by using X-ray diffraction, Fourier-transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray, and nitrogen adsorption-desorption isotherms. It was found that the nanorod manganese oxide was highly dispersed onto the diatomite porous matrix. The specific surface area of the obtained manganese oxide/diatomite (SBET=68.5 m2 g−1) is larger than that of natural diatomite (SBET=55.4 m2 g−1). It was utilized to remove Pb(II) in aqueous solutions. It exhibits an excellent Pb(II) adsorption capacity. The adsorption data fits well with the pseudo-second-order kinetics model, and the adsorption process is endothermic and spontaneous with an activation energy of 41.56 kJ mol−1 and follows the Freundlich isotherm model. The Mn/diatomite adsorption capacity for Pb(II) is 81.42 mg g−1, calculated with the Langmuir model. In addition, the adsorption mechanism of Pb(II) onto Mn/diatomite is also addressed.